STRATEGI PENGEMBANGAN EKOWISATA CURUG MRAWU TIENG MENUJU DESA MANDIRI - Ratna Suryani; Radhitya Purwa Nugraha (Medikonis, 2020)
ABSTRACT This study aims to determine the potentiality that exists in the Curug Mrawu Tieng Ecotourism area and its relationship with the Index of Developing Villages (IDV) in the Batur village. The assessment is carried out all of the carrying capacity for the suitability of nature tourism and also analyzes the internal and external environment of the area, as well as calculating the values of the building village indicators to obtain a tourism area development strategy and the development of village independence. This research is descriptive study using qualitative methods. Data collection techniques namely, observation, interviews and documentation. For analytical tools using SWOT analysis and assessing Index of Developing Villages. The results of this study indicate that the assessment of the carrying capacity of the area is very adequate to be a tourist area. The assessment of tourist objects and natural attractions included in Good Categories. The regional analysis for tourism are at Potential Intervals. The IDV Batur villages are in the classification Developing Village. The SWOT analysis result area can be used to improve the assessment of the IDV indicators, namely: SO (Strengths-Opportunities) strategy with Environmental Resilience Index and Economic Resilience Index; WO (Weakness-Opportunities) strategy with Economic Resilience Index And Social Resilience Index; ST (Strengths-Threats) strategy with Economic Resilience Index and Social Resilience Index; and WT (Weakness-Threats) strategy with Environmental Resilience Index.